Late Neogene benthic foraminifera and stable carbon isotope record of the blake Outer Ridge - Ajoy K Bhaumik; Anil K Gupta; Ellen Thomas (PANGAEA, 2011)
Carbon isotope and benthic foraminiferal data from Blake Outer Ridge, a sediment drift in the western North Atlantic (Ocean Drilling Program Sites 994 and 997, water depth ~ 2800 m), document variability in the relative volume of Southern Component (SCW) and Northern Component Waters (NCW) over the last 7 Ma. SCW was dominant before ~5.0 Ma, at ~3.6-2.4 Ma, and 1.2-0.8 Ma, whereas NCW dominated in the warm early Pliocene (5.0-3.6 Ma), and at 2.4-1.2 Ma. The relative volume of NCW and SCW fluctuated strongly over the last 0.8 Ma, with strong glacial-interglacial variability. The intensity of the Western Boundary Undercurrent was positively correlated to the relative volume of NCW. Values of Total Organic Carbon (TOC) were > 1.5% in sediments older than ~ 3.8 Ma, and not correlated to high primary productivity indicators, thus may reflect lateral transport of organic matter. TOC values decreased during the intensification of the Northern Hemisphere Glaciation (NHG, 3.8-1.8 Ma). Benthic foraminiferal assemblages underwent major changes when the sites were dominantly under SCW (3.6-2.4 and 1.2-0.8 Ma), coeval with the extquotesingleLast Global Extinction extquotesingle of elongate, cylindrical deep-sea benthic foraminifera, which has been linked to cooling, increased ventilation and changes in the efficiency of the biological pump. These benthic foraminiferal turnovers were neither directly associated with changes in dominant bottom water mass nor with changes in productivity, but occurred during global cooling and increased ventilation of deep waters associated with the intensification of the NHG.
Supplement to: Bhaumik, AK et al. (2011): Blake Outer Ridge: Late Neogene variability in paleoceanography and deep-sea biota. Palaeogeography, Palaeoclimatology, Palaeoecology, 302(3-4), 435-451, https://doi.org/10.1016/j.palaeo.2011.02.004